Net profit how to succeed in digital business - Soskin, David, 1954- (New York : Wiley, 2010)
"Online business can be a goldmine - or a minefield. David Soskin, former CEO of Cheapflights and Chairman of mySupermarket.co.uk, has faced all the problems thrown up by building a business on the Internet, and solved them. Here, he shows you how to: Convert a brilliant idea into something that actually pays Get the funding you need to expand Build a great team of staff and advisers Keep the cash flowing Go global! Net Profit provides much needed inspiration and reassurance for would-be start ups and established businesses who want to do more online"--
"Online business is big again. Following the 2002-2003 dot com crash, there was a great deal of scepticism about the exuberance and hype that had led to the crash"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Electronic commerce; Success in business; Electronic books